A phase I trial of WRSS1, a Shigella sonnei live oral vaccine in Bangladeshi adults and children. Issue 6 (3rd June 2019) - Raqib, Rubhana; Sarker, Protim; Zaman, K.; Alam, Nur Haque; Wierzba, Thomas F.; Maier, Nicole; Talukder, Kaisar; Baqui, Abdullah Hel; Suvarnapunya, Akamol E.; Qadri, Firdausi; Walker, Richard I.; Fix, Alan; et al.
ABSTRACT: Shigella sonnei live vaccine candidate, WRSS1, which was previously evaluated in US, Israeli and Thai volunteers, was administered orally to Bangladeshi adults and children to assess its safety, clinical tolerability and immunogenicity. In a randomized, placebo-controlled, dose-escalation, age-descending study, 39 adults (18–39 years) and 64 children (5–9 years) were enrolled. Each adult cohort (n = 13) received one dose of 3x10 4, or three doses of 3 × 10 5 or 3 × 10 6 colony forming unit (CFU) of WRSS1 (n = 10) or placebo (n = 3). Each child cohort (n = 16) received one dose of 3x10 3, or three doses of 3x10 4, 3x10 5, or 3 × 10 6 CFU WRSS1 (n = 12) or placebo (n = 4). WRSS1 elicited mostly mild and transient reactogenicity events in adults and children. In the 3 × 10 6 dose group, 50% of the adults shed the vaccine; no shedding was seen in children. At the highest dose, 100% of adults and 40% of children responded with a ≥ 4-fold increase of S. sonnei LPS-specific IgA antibody in lymphocyte supernatant (ALS). At the same dose, 63% of adults and 70% of children seroconverted with IgA to LPS, while in placebo, 33% of adults and 18% of children seroconverted. Both the vaccinees and placebos responded with fecal IgA to LPS, indicating persistent exposure to Shigella infections. In conclusion, WRSS1 was found safe up to 10 6 CFU dose and immunogenic in adults and children in Bangladesh. These data indicate that live, oral Shigella vaccine candidates, including WRSS1 can potentially be evaluated in toddlers and infants (<2 years of age), who comprise the target population in an endemic environment.